SIFAT KAPASITANSI PARALEL, INDUKTANSI PARALEL, DAN KONDUKTANSI BISKUIT (KERAS) DALAM KEMASAN ALUMUNIUM FOIL DAN PLASTIK - Erna Rusliana M Saleh (Jurnal Biofisika, 2012)
Knowledge of the dielectric properties of food is very important in research, modeling and development of thermal treatment. Associated with biscuits, crackers knowledge of dielectric properties will be useful for many applications for them to predict future food kadaluarsanya. Terdapat three dielectric parameters measured were parallel capacitance , inductance and parallel conductance on biscuits (hard) with aluminum foil and plastic packaging . The third parameter to measure the dielectric used HIOKI 3532-50 LCR LCR - meter Hitester with pegukuran frequency 42 Hz - 5 MHz in constant current (Constant Current) 1.0 . Results parallel capacitance and inductance measurement parallel pattern looks biscuits decreased with increasing measurement frequency, while the conductance ascending pattern seen with increasing frequency. Biscuits with aluminum foil packaging has a parallel capacitance value 7x10-6 to 22x10-4 Farad, parallel inductance 0.000151 to 3.089 x10 9 and conductance 0.082533 to 22.285529 Siemens. While packing biscuits with platik have capacitance values 5x10-6 to 2.98 x 10-4 Farad, parallel inductance 0.000216 to 236.026 x 10 9 and conductance 0.073310 to 31.210734 Siemens